Food markets in Russia: Dynamics of their integration - Konstantin Gluschenko; Alexandra Khimich (Institute for Advanced Studies (IHS), 2007)
In the context of integrated market, a price of any product in regions depends on its demand in a national market rather than in a regional one. Applying the econometric model based on this theoretical statement, the paper assesses to degree the markets of some food products are integrated. The fact that since nearly 1994 the growth of segmentation in such markets changes to the tendency of their integration has been observed. We conclude that there is an integrated food market in Russia; and its integration has been just the same as that one in the countries of developed market economy.
Keywords: K49; P22; P37; R19; 330; price dispersion; market integration; food markets; Russia; Russian regions; Preisdifferenzierung; Marktintegration; Nahrungsmittelmarkt; Russland